2021
DOI: 10.1038/s41598-021-86521-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between second to fourth digit ratio, cortisol, vitamin D, and body composition among Polish children

Abstract: Associations between body characteristics (body composition: fat mass, muscle mass, cell, and water mass as well as body proportion—BMI), the 2D:4D digit ratio, and the concentrations of cortisol and vitamin (25-OH)D among Polish children have not been studied before. A total of 133 (73 girls and 60 boys) healthy Polish children aged 7–11 years were examined. The investigation was divided into three parts: measuring (the length of the second and fourth fingers in both hands, body composition, and body height a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Consistent with previous research [22][23][24] ,our study found no significant correlation between Vitamin D levels and various measures of body composition, including BMI, BFM, SLM, and SMM.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous research [22][23][24] ,our study found no significant correlation between Vitamin D levels and various measures of body composition, including BMI, BFM, SLM, and SMM.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Klimek et al, based on studies performed in men, indicate that low 2D:4D (stronger prenatal androgenization) is associated with higher body weight in childhood and adolescence 44 . At the same time, other studies of children and adolescents from various populations did not confirm the relationship between 2D: 4D and relative body weight 45 , 46 .…”
Section: Discussionmentioning
confidence: 79%
“…Since it is known that testosterone is associated with muscle mass growth and estrogen affects adipogenesis, the 2D:4D ratio was evaluated to see if it could be an indicator of fat mass, muscle mass and body proportions in children and it was shown that it could be an indicator for muscle mass development in girls in early childhood 22 . In other studies on children, the relationship between 2D:4D ratio and cortisol, vitamin D level and body composition, and the relationship between 2D:4D ratio and fitness level were evaluated 23 , 24 . There are studies suggesting that prenatal sex steroid exposure may be a risk factor for migraine in adults and may be associated with birth weight, BMI and muscle strength in children 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%